Schools of positive parenting a pedagogical strategy since for professional practices in the Social Sciences (Revista Innova Educación, 2020)
The work raises the reflection of schools of positive parenting as pedagogical strategies from the scenarios of professional practices and establishes the possibility of expression of professional intervention, as a diverse process; where, training combines skill, theory and practice. This study seeks to describe the pedagogical processes using the mixed method in research. Data collection was given through 7 semi-structured interviews with fields of professional practice, 25 interviews with students in formation of the Social Work program, and the implementation of 2 methodological guides aimed at the general population and institutional officials in the municipalities of Soacha and Sibaté. Therefore, basing pedagogy on the social side is necessary to count different methods that allow making sense and purpose for professional intervention. Accordingly, trying to understand and explain new pedagogical strategies becomes a fundamental need to guide social interventions.
Keywords: Pedagogical strategy; social intervention; skills; positive parenting and practice